Sistema totalmente não-invasivo para determinação da velocidade de rotação do eixo, torque e rendimento em motores de indução em operação - Silva, Julio Cesar da (2018)
Three-phase induction motors (TIM) are considered the core of the plants, being present in almost every production process and being responsible for two-thirds of the electric energy consumption in the industrial environment. Monitoring the magnitudes of threephase induction motors, such as torque, speed, and efficiency are essential to maintaining an operating productive process. Having a precise speed value permits to get a greater control over the process in which the TIM is located. Torque monitoring allows avoiding shaft breaks and stops, besides reducing maintenance costs. Efficiency monitoring allows establishing an energy balance of the three-phase induction motor, reducing electric energy waste. However, the equipment utilized to perform these evaluations is expensive and a lot of times it is unfeasible due to difficulties to couple them to the TIM, which results in a great invasiveness of the motor. In the present work, a new non-invasive system based on the analysis of the sound from the operating TIM was developed, allowing to estimate speed, torque and efficiency. The air gap torque, due to its low rate of invasiveness of the motor, was utilized as a comparison method, from which torque and efficiency were estimated. In order to validate the new method, it was utilized an automated torque test bench in which speed values, torque, and efficiency were measured directly from the TIM shaft. The programs Labview™ and Matlab were used to acquire the signals and to process the data, respectively. After the analysis of the collected data, it was possible to compare the implemented methods and to validate the proposed method.